2014
DOI: 10.1186/1742-2094-11-80
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immune cell infiltration and increased pro-inflammatory mediators in the brain of Type 2 diabetic mouse model infected with West Nile virus

Abstract: BackgroundDiabetes is a significant risk factor for developing West Nile virus (WNV)-associated encephalitis (WNVE) in humans, the leading cause of arboviral encephalitis in the United States. Using a diabetic mouse model (db/db), we recently demonstrated that diabetes enhanced WNV replication and the susceptibility of mice to WNVE. Herein, we have examined immunological events in the brain of wild type (WT) and db/db mice after WNV infection. We hypothesized that WNV-induced migration of protective leukocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 62 publications
(140 reference statements)
0
76
0
Order By: Relevance
“…63 The link between glucose intolerance and central inflammation was reported by Kumar M (2014), showing that in the genetic diabetic model (db/db mice) displays increase in mRNA and protein levels of key chemokines such as CXCL10, CXCL1, CCL2, CCL5, CCL3 and G-CSF, and cytokines such as IL-1β, TNF, IL-6, IFNγ and IL-1α compared to WT mice, suggesting that metabolic compromise correlate with central immune response activation despite hypercaloric state. 64 Also, initial research by Velloso's group reported that specific low-grade chronic inflammation modulates body glucose homeostasis, supporting that hypothalamic TNFα administration to rats leads to hyperinsulinemia and insulin resistance in liver and skeletal muscle, 65 and also generates pancreas dysfunction. 66, 67 Of note, these effect are dependent on parasympathetic signals delivered by the vagus nerve to pancreas or liver.…”
Section: Inflammation Of the Nervous System During Obesity Is Key In mentioning
confidence: 97%
“…63 The link between glucose intolerance and central inflammation was reported by Kumar M (2014), showing that in the genetic diabetic model (db/db mice) displays increase in mRNA and protein levels of key chemokines such as CXCL10, CXCL1, CCL2, CCL5, CCL3 and G-CSF, and cytokines such as IL-1β, TNF, IL-6, IFNγ and IL-1α compared to WT mice, suggesting that metabolic compromise correlate with central immune response activation despite hypercaloric state. 64 Also, initial research by Velloso's group reported that specific low-grade chronic inflammation modulates body glucose homeostasis, supporting that hypothalamic TNFα administration to rats leads to hyperinsulinemia and insulin resistance in liver and skeletal muscle, 65 and also generates pancreas dysfunction. 66, 67 Of note, these effect are dependent on parasympathetic signals delivered by the vagus nerve to pancreas or liver.…”
Section: Inflammation Of the Nervous System During Obesity Is Key In mentioning
confidence: 97%
“…In the case of in vitro WNV infection of endothelium, intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1 and E-selectin appeared to be upregulated (Table 2) [32,45]. The importance of ICAM-1 and E-selectin for leukocytic neuro-infiltration post-WNV inoculation is further supported by in vivo evidence [46,48]. Expression of certain integrins, such as very late antigen (VLA)-4 on LyC6 hi monocyte-derived macrophages, may also be important in aiding migration of particular leukocytes into the CNS in vivo [49].…”
Section: Hematogenous Route Of Neuroinvasionmentioning
confidence: 97%
“…6D-- Prior to our studies, the insulin signaling pathway had not been specifically linked to 305 host immunity to WNV. Intriguingly, however, diabetes mellitus has been shown to 306 increase risk of WNV infection (Nash et al, 2001) and, in mouse models of the disease, 307 leukocyte and T cell recruitment are decreased and WNV replication and 308 neuroinvasiveness are increased in the absence of insulin (Kumar et al, 2012(Kumar et al, , 2014. These 309 observations are mirrored in malaria parasite infection.…”
Section: Introduction 39mentioning
confidence: 99%